Effects of Peanut Consumption on Cardiometabolic Risk Factors in a Chinese Population: A Randomized, Controlled Trial (P08-041-19). (24th October 2019) - Wang, Di; Liu, Xiaoran; Sun, Liang; Niu, Zhenghua; Chen, Shuangshuang; Xiong, Quan; Malik, Vasanti; Hu, Frank; Lin, Xu
Abstract: Objectives: To determine the effect of peanut consumption, as part of the diet on cardiometabolic risk factors and Metabolic Syndrome (MetS) in a Chinese population at risk for developing type 2 diabetes. Methods: We recruited 224 participants (men and women, ages 46 ± 10 y, BMI 28.0 ± 3.1 kg/m 2 ) with central obesity plus at least one additional MetS risk factor. In this randomized, parallel-arm, controlled study, participants were supplemented with either lightly salted peanuts, 2oz (56 g) per day or a calorie-matched control snack (refined grains) for 12 weeks. Peanuts and control snacks were consumed between meals. Anthropometric and metabolic measurements were assessed at baseline, week 6 and week 12. We used paired Student's t-tests to examine within-treatment differences and multivariable linear regression for between-treatment differences with the models adjusted for age, sex and baseline BMI (with the exception of analysis on waist circumference [WC], body weight and BMI). Multivariate logistic regression was used to calculate the reversion rate of MetS. Results: The peanut group and the control group had similar energy intake (peanut: 1872 ± 433 kcal, control: 1906 ± 400 kcal). There were no differences observed between the two groups on WC, body weight, and BMI. Compared to baseline, the peanut group had small but significant reductions in WC (–0.88 ± 0.32 cm, P  = 0.006), body weight (–0.41 ± 0.16 kg, P  = 0.01), and BMI (–0.14 ± 0.06 kg/m 2, P  = 0.01) at week 12. Both groups decreased fasting glucose levels (peanut: 0.32 ± 0.06 mmol/L, P  < 0.001; control: 0.28 ± 0.05 mmol/L, P  < 0.001) and increased HDL-C levels (peanut: 0.05 ± 0.02 mmol/L, P  = 0.001; control: 0.05 ± 0.02 mmol/L, P  = 0.002) after 12 weeks. The peanut group decreased triglycerides by −0.34 ± 0.13 mmol/L ( P  = 0.009) at week 6. There were no effects on LDL-C, total cholesterol or blood pressure. The peanut group had a greater reversion rate of MetS compared to the control group at week 6 (31.7% vs. 17.9%, P  = 0.04, Figure 1 ), which attenuated at week 12 ( P  = 0.10). Conclusions: Adding 2oz of peanuts per day to the diet for 12 weeks did not promote weight gain among Chinese adults at risk for type 2 diabetes. Consumption of peanuts may help ameliorate MetS, suggesting that peanuts may be a healthful snack option relative to refined grains. Funding Sources: This study was supported by the Chinese Academy of Sciences (Grant/Award Number: KJZD-EW-G20-02), and an in kind donation from the Peanut Institute. The finding source had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Supporting Tables, Images and/or Graphs